Costs and Its Determinants in Pituitary Tumour Surgery - Dekkers, Alies J.; de Vries, Friso; Zamanipoor Najafabadi, Amir H.; van der Hoeven, Emmy M.; Verstegen, Marco J. T.; Pereira, Alberto M.; van Furth, Wouter R.; Biermasz, Nienke R. (Frontiers in Endocrinology, 2022)
Purpose: Value-based healthcare (VBHC) provides a framework to improve care by improving patient outcomes and reducing healthcare costs. To support value-based decision making in clinical practice we evaluated healthcare costs and cost drivers in perioperative care for pituitary tumour patients. Methods: We retrospectively assessed financial and clinical data for surgical treatment up to the first year after surgery of pituitary tumour patients treated between 2015 and 2018 in a Dutch tertiary referral centre. Multivariable regression analyses were performed to identify determinants of higher costs. Results: 271 patients who underwent surgery were included. Mean total costs (SD) were €16339 (13573) per patient, with the following cost determinants: surgery time (€62 per minute; 95%CI: 50-74), length of stay (€1331 per day; 95%CI: 1139-1523), admission to higher care unit (€1215 in total; 95%CI: 46413-17895), emergency surgery (€10363 higher than elective surgery; 95%CI: 1422-19305) and postoperative cerebrospinal fluid leak (€14232; 95%CI: 9667-18797). Intradural (€7128; 95%CI: 10421-23836) and combined transsphenoidal/transcranial surgery (B: 38494; 95%CI: 29191-47797) were associated with higher costs than standard. Further, higher costs were found in these baseline conditions: Rathke’s cleft cyst (€9201 higher than non-functioning adenoma; 95%CI: 1173-17230), giant adenoma (€19106 higher than microadenoma; 95%CI: 12336-25877), third ventricle invasion (€14613; 95%CI: 7613-21613) and dependent functional status (€12231; 95%CI: 3985-20477). In patients with uncomplicated course, costs were €8879 (3210) and with complications €17551 (14250). Conclusions: Length of hospital stay, and complications are the main drivers of costs in perioperative pituitary tumour healthcare as were some baseline features, e.g. larger tumors, cysts and dependent functional status. Costs analysis may correspond with healthcare resource utilization and guide further individualized care path development and capacity planning.